Sosialisasi Penggunaan Software SimaPro Untuk Analisis Siklus Hidup dalam Konteks Keberlanjutan Lingkungan - Indah, A. Besse Riyani; Bahri, Syamsul; Amar, Kifayah; Asmal, Sapta; Hanafi, Rosmalina; Rusman, Muhammad; Hadijah, A. Nurul Izzah; Sakti, Fajriani; Afifudin, Mohammad Thezar; Sahar, Dian Pratiwi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
This community service activity aims to enhance the understanding and skills of the Dinas Lingkungan Hidup (DLH) of Pangkep Regency in using SimaPro software for Life Cycle Assessment (LCA) within the context of environmental sustainability. Currently, DLH Pangkep faces challenges in conducting environmental impact assessments manually, which require significant human resources, time, and costs. Through the socialization and training of SimaPro usage, this activity aims to improve the efficiency and effectiveness of DLH in assessing the environmental impact of production systems. The implementation methods include needs assessment, activity planning, an opening session, practical training in using SimaPro, discussions and Q&A sessions, as well as evaluation and feedback. The expected outcomes include increased understanding and skills of participants in using SimaPro for LCA, along with scientific publications. This activity is expected to enhance the capacity of DLH Pangkep in conducting more comprehensive and efficient environmental impact assessments, thereby supporting DLH in making more sustainable decisions related to environmental policies in Pangkep Regency. Quantitative analysis of pre-test and post-test results shows a significant improvement in participants' understanding and skills, especially in using SimaPro, with a 191.7% increase. This indicates the success of the training in enhancing DLH Pangkep's competency in environmental impact assessment.